Vertical and horizontal variation of elemental contamination in sediments of Hooghly Estuary, India. Issue 1 (15th August 2016) - Ghosh, Somdeep; Ram, Shidharth Sankar; Bakshi, Madhurima; Chakraborty, Anindita; Sudarshan, Mathummal; Chaudhuri, Punarbasu
Abstract: Hooghly Estuary along with the Sunderban mangroves forms one of the most diverse ecosystems in the world. We investigated the vertical and horizontal distribution of elements at nine sampling locations in this estuary for assessing the degree of elemental contamination. The elemental concentrations were analyzed by an Energy Dispersive X-ray Flurosence spectrometer (EDXRF). A higher enrichment factor (EF) value of trace elements (V, Cr, Mn, Fe, Ni, Cu and Zn) is evident considering all the sampling locations. Geo-accumulation index (Igeo ) values of all the sampling locations and core depth reveals Cr and Cu are under Igeo Class I level of contamination. The value of the pollution load index (PLI) varies between 0.94–1.65 with maximum at Chemaguri and minimum at Haldi Estuary and Petuaghat. The overall variation in elemental concentration may be due to differential discharge pattern of storm water and agricultural run-off, industrial effluent and domestic sewage. Highlights: Pollution status of Hooghly estuary sediments was studied. Enrichments of trace elements (Cr, Cu, Mn, Fe, V, Zn and Ni) were observed in sediments. Strong correlation was observed between elements in sediments. Pollution load index is maximum at Chemaguri (S8) mouth of the Hooghly estuary. Sediment quality indices indicate the sediment quality to be moderately contaminated and suffering from gradual degradation.